War's ends : human rights, international order, and the ethics of peace - Murphy, James G., 1953- (Georgetown University Press, 2014)
Before military action, and even before mobilization, the decision on whether to go to war is debated by politicians, pundits, and the public. As they address the right or wrong of such action, it is also a time when, in the language of the just war tradition, the wise would deeply investigate their true claim to jus ad bellum (""the right of war""). Wars have negative consequences, not the least impinging on human life, and offer infrequent and uncertain benefits, yet war is part of the human condition. James G. Murphy's insightful analysis of the jus ad bellum criteria-competent authority, j